The Quarter Prone Position Increases Oxygen Saturation in Premature Infants Using Continuous Positive Airway Pressure. (30th November 2017) - Utario, Yossy; Rustina, Yeni; Waluyanti, Fajar Tri
ABSTRACT: A primary problem that occurs in premature infants is oxygenation disorders, thus requiring respiratory support, including continuous positive airway pressure (CPAP). The effectiveness of CPAP can be improved by adjusting the body's position, so the aim of this study was to examine the effect of the quarter prone position on the oxygenation status of preterm infants using CPAP. This study used a randomized controlled trial with a crossover design. A group of 15 preterm infants receiving CPAP was selected, and randomization of allocation was done to divide the respondents into the intervention group (quarter prone) or the control group (supine). Oxygenation status was measured using an observation form, and the result showed a significant difference in the oxygen saturation levels of premature infants using CPAP in the quarter prone group compared to that in the supine group ( p  = .045). The quarter prone position was effective for improving the oxygenation status of premature infants using CPAP. It is recommended that the quarter prone position be applied as part of nursing care in neonatal nursing.